Partial Least Square-Structural Equation Modeling (PLS-SEM) untuk mengukur ekspektasi penggunaan repositori lembaga: Pilot studi di UIN Syarif Hidayatullah Jakarta - Agus Rifai (Al Maktabah, 2015)
Since the institutional repositories was introduced, and its advantages in increasing the institution performances has been recognized, many universities in Indonesia has been developing the repositories system for preserving and disseminating their intellectual outputs. However, despite of its development, the existing of repository system is less used. It is alleged that lecturers are not aware and reluctant due to their task complexity. In addition, user expectancy should be observed in relation with the use of institutional repositories. The purpose of this paper is to examine a limited sample data on the relationship between user expectancy and the use of institutional repositories in higher education institutions in Indonesia. A pilot study is conducted with 50 university lecturers at Syarif Hidayatullah Jakarta. This study investigates as well as predicts the relationship between users’ expectancies and the use of institutional repositories. Structural analysis is employed by using PLS-SEM (Partial Least Square-Structural Equation Modeling) approach. SmartPLs 2.0 software is used in the analysis. The results indicated that user expectancy has a significant relationship with the use of institutional repositories by its contribution up to 57.8 %